Is delayed graft function associated with ureteral stenosis in the kidney transplant recipient? A case-control study - Cayetano-Alcaraz, Axel; Rodriguez-Alvarez, Juan Sebastian; Vilatobá-Chapa, Mario; Alberú-Gómez, Josefina; Gabilondo-Pliego, Bernardo; Rodríguez-Covarrubias, Francisco; Morales-Buenrostro, Luis Eduardo; Méndez-Probst, Carlos Enrique (Canadian Urological Association Journal, 2019)
Introduction: Ureteral stricture (US) in the kidney transplant recipient is a rare complication that can lead to morbidity and graft loss. Risk factor recognition is crucial in the prevention and management of this entity. Delayed graft function (DGF), as defined by the need for dialysis in the first week after transplantation, has been proposed as a risk factor in previous studies. Our objective is to determine the impact of DGF in US development in kidney transplant patients. Methods: We designed a matched case-control study. US cases in kidney transplant recipients were identified in the 2008–2017 period. We defined US as the rise in serum creatinine associated with findings suggesting obstruction in ultrasound, scintigraphy, or retrograde pyelogram; any other cause of graft dysfunction was excluded. Controls were defined as kidney transplant recipients from the same population and period without US, matched in a 1:2 fashion by age, sex, and donor type. Results: From 532 kidney transplant patients, 31 cases and 62 controls were included. Cumulative US incidence was 58 per 1000 cases. When calculating for odds ratio (OR), postoperative urinoma (OR 3.2; 95% confidence interval [CI] 2.36–4.37) and ureteral duplication (OR 3.29; 95% CI 2.40–4.51) were associated with an increased risk for US, while DGF was not found to be statistically significant as a risk factor (OR 3.3; 95% CI 0.96–11.52). No statistically significant differences were found between groups in other pre- and post-transplant-related factors. Conclusions: DGF was not associated with US in our cohort; however, ureteral duplication and postoperative urinoma were associated with an increased risk of graft ureteral stenosis development.